Re-inventing the postcolonial (in the) metropolis (Brill, 2016)
The notion of the postcolonial metropolis has gained prominence in the last two decades both within and beyond postcolonial studies. Disciplines such as sociology and urban studies, however, have tended to focus on the economic inequalities, class disparities, and other structural and formative aspects of the postcolonial metropolises that are specific to Western conceptions of the city at large. It is only recently that the depiction of postcolonial metropolises has been addressed in the writings of Suketu Mehta, Chris Abani, Amit Chaudhuri, Salman Rushdie, Aravind Adiga, Helon Habila, Sefi Atta, and Zakes Mda, among others. Most of these works probe the urban specifics and physical and cultural topographies of postcolonial cities while highlighting their agential capacity to defy, appropriate, and abrogate the superimposition of theories of Western modernity and urbanism. These ASNEL Papers are all concerned with the idea of the postcolonial (in the) metropolis from various disciplinary viewpoints, as drawn from a great range of cityscapes (spread out over five continents)
10.1163/9789004328761
Keywords: Postcolonialism; Metropolitan areas